2021
DOI: 10.3389/fonc.2021.706503
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Programmed Death Ligand-1 on Tumor-Infiltrating Immune Cells in “High-Risk” Patients Following Radical Cystectomy: A Retrospective Cohort Study

Abstract: PurposeThe aim of this study is to investigate the prognostic role of programmed death ligand-1 (PD-L1) on tumor-infiltrating immune cells (TIICs) in patients after radical cystectomy (RC) for bladder cancer (BCa).Materials and MethodsWe retrospectively reviewed 92 “high-risk” (≥pT3a and/or pN+) patients who underwent RC for BCa, without adjuvant chemotherapy (AC), between April 2014 and December 2019. PD-L1 on TIICs was measured only using the VENTANA (SP-142) immunohistochemistry assay. Patients were categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previous studies have reported the development of an exhausted immune state in the tumor stroma of UC [24], and positive PD-L1 expression in TICs showing a significantly shorter RFS compared to negative PD-L1 expression [24,27]. Therefore, we previously reported that positive PD-L1 expression in TICs was significantly associated with shorter RFS in "high-risk" (≥pT3a and/or pN+) UC and may be used as a prognostic biomarker of tumor recurrence following RC irrespective of adjuvant chemotherapy [28,29]. Additionally, in our study, we found that positive PD-L1 expression in TICs was significantly associated with an increased risk of tumor recurrence in patients with MPUC or UCSD.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have reported the development of an exhausted immune state in the tumor stroma of UC [24], and positive PD-L1 expression in TICs showing a significantly shorter RFS compared to negative PD-L1 expression [24,27]. Therefore, we previously reported that positive PD-L1 expression in TICs was significantly associated with shorter RFS in "high-risk" (≥pT3a and/or pN+) UC and may be used as a prognostic biomarker of tumor recurrence following RC irrespective of adjuvant chemotherapy [28,29]. Additionally, in our study, we found that positive PD-L1 expression in TICs was significantly associated with an increased risk of tumor recurrence in patients with MPUC or UCSD.…”
Section: Discussionmentioning
confidence: 93%